Pattern of subcutaneous fat during follow‐up of a cohort of North Indian children with Kawasaki disease: a preliminary study. (11th February 2014) - Suthar, Renu; Singh, Surjit; Bhalla, Anil Kumar; Attri, Savita Verma
Abstract Aim Kawasaki disease (KD) has been associated with abnormal lipid profiles. The latter, in turn, have been linked to changes in subcutaneous fat. In this comparative cross‐sectional study we have quantified distribution of subcutaneous fat during follow‐up of a cohort of North Indian children with KD. Method We compared 35 KD children (at least 2 years after disease) and 33 healthy controls. Study parameters included weight, height and skinfold thickness (SFT) over biceps, triceps, midaxillary, subscapular, medial calf and suprailiac areas. Waist and hip circumferences were also recorded. All parameters were measured four times at 6‐monthly intervals using standardized techniques. Serum lipids were assayed in the study group. Results Study children were enrolled 3.7 ± 2.5 years after KD and mean age at enrolment was 8.26 ± 3.65 years. Suprailiac SFT measured higher in boys with KD (P ≤ 0.05). Biceps SFT was higher in the study group, but the difference was not significant. Other SFT were not affected. Waist and hip circumference was higher in the study group than controls (P ≤ 0.05). Waist/hip circumference ratio was not affected. Serum low‐density lipoprotein cholesterol (LDL‐C) and triglycerides were higher in the study group as compared to historical controls (95.60 ± 36.12 and 129.40 ± 64.62 mg/dL vs. 80.10 ± 2.20 and 91.1 ± 29.85; P ≤ 0.05). Total cholesterol and high‐density lipoprotein cholesterol levels remained unaffected. Conclusion Children with KD (especially boys) had increased subcutaneous fat deposition in the suprailiac region and waist, during follow‐up. Serum LDL‐C and triglycerides were elevated. KD children may have a tendency to develop central obesity. Further studies, with longer follow‐up, would be necessary to show whether this has implications for development of coronary artery disease later in life.